Atomic Scale Structural Characterization of Epitaxial (Cd, Cr)Te Magnetic Semiconductor. (7th June 2017) - Bonef, Bastien; Boukari, Hervé; Grenier, Adeline; Mouton, Isabelle; Jouneau, Pierre-Henri; Kinjo, Hidekazu; Kuroda, Shinji
Abstract: A detailed knowledge of the atomic structure of magnetic semiconductors is crucial to understanding their electronic and magnetic properties, which could enable spintronic applications. Energy-dispersive X-ray spectrometry (EDX) in the scanning transmission electron microscope and atom probe tomography (APT) experiments reveal the formation of Cr-rich regions in Cd1− x Cr x Te layers grown by molecular beam epitaxy. These Cr-rich regions occur on a length scale of 6–10 nm at a nominal Cr composition of x =0.034 and evolve toward an ellipsoidal shape oriented along <111> directions at a composition of x =0.083. Statistical analysis of the APT reconstructed volume reveals that the Cr aggregation increases with the average Cr composition. The correlation with the magnetic properties of such (Cd, Cr)Te layers is discussed within the framework of strongly inhomogeneous materials. Finally, difficulties in accurately quantifying the Cr distribution in the CdTe matrix on an atomic scale by EDX and APT are discussed.